A comparative first-principles study on electronic structures and mechanical properties of ternary intermetallic compounds Al8Cr4Y and Al8Cu4Y: Pressure and tension effects. (November 2016) - Yang, Wenchao; Pang, Mingjun; Tan, Yong; Zhan, Yongzhong
Abstract: An investigation into the bulk properties, elastic properties and Debye temperature under pressure, and deformation mode under tension of Al8 Cu4 Y and Al8 Cr4 Y compounds was investigated by using first principles calculations based on density functional theory. The calculated lattice constants for the ternary compounds (Al8 Cu4 Y and Al8 Cr4 Y) are in good agreement with the experimental data. It can be seen from interatomic distances that the bonding between Al1 atom and Cr, Y, and Al2 atoms in Al8 Cr4 Y are stronger than Al8 Cu4 Y. The results of cohesive energy show that Al8 Cr4 Y should be easier to be formed and much stronger chemical bonds than Al8 Cu4 Y. The bulk modulus B, shear modulus G, Young's modulus E and Poisson's ratio ν can be obtained by using the Voigt–Reuss–Hill averaging scheme. From the results of elastic properties, Al8 Cr4 Y has the stronger mechanical behavior than Al8 Cu4 Y. Our calculations also show that pressure has a greater effect on mechanical behavior for both compounds. The ideal tensile strength are obtained by stress-strain relationships under [001](001) uniaxial tensile deformation, which are 15.4 and 23.4 GPa for Al8 Cu4 Y and Al8 Cr4 Y, respectively. The total and partial density of states and electron charge density under uniaxial tensile deformations for Al8 Cu4 Y and Al8 Cr4 Y compounds are also calculated and discussed in this work. Graphical abstract: Highlights: Al8 Cr4 Y should be easier to be formed and much stronger chemical bonds than Al8 Cu4 Y. Al8 Cr4 Y has the stronger mechanical behavior than Al8 Cu4 Y. Al8 Cr4 Y possess a better thermal conductivity than Al8 Cu4 Y. The ideal tensile strengths for Al8 Cu4 Y and Al8 Cr4 Y are 15.4 and 23.4 GPa under [001](001) uniaxial tensile deformation, respectively.